Pengaruh Green Accounting Terhadap Kinerja Keuangan Perusahaan Sektor Industri Dasar dan Kimia di BEI Periode 2021-2024 - Rona Monika; Subadriyah Subadriyah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The research was conducted to examine the impact of green accounting practices on financial performance. This study employs a quantitative method utilizing secondary data sourced from the Indonesia Stock Exchange, official company websites, and the PROPER list from the Ministry of Environment. The research focuses on companies in the basic industry and chemical sectors listed on the IDX from 2021 to 2024. The research sample was selected using purposive sampling based on specific criteria. Data were processed using SPSS software with multiple linear regression techniques. The dependent variable, financial performance, was measured using ROA (Return on Assets). The research findings reveal that green accounting, proxied by environmental costs (X1), has a significant positive influence on financial performance with a significance value of 0.050, while environmental performance (X2) shows no significant impact on financial performance due to a significance value of 0.647, and environmental disclosure (X3) has a significant positive influence on financial performance with a significance value of 0.040.